Synthesis, Crystal Structures, and Antimicrobial and Antitumor Studies of Two Zinc(II) Complexes with Pyridine Thiazole Derivatives - Zou Xun-Zhong; Feng An-Sheng; Zeng Fu-Ran; Lai Min-Cheng; Liao Yan-Zhi; Mei Meng; Li Yu (Bioinorganic Chemistry and Applications)
Two pyridine thiazole derivatives, namely, 4-(pyridin-2-yl)-2-(2-(pyridin-2-ylmethylene)hydrazinyl)thiazole (L1) and 4-(pyridin-3-yl)-2-(2-(pyridin-4-ylmethylene)hydrazinyl)thiazole (L2), were afforded by a cyclization reaction between α-haloketone and thioamide, and their Zn(II) complexes were prepared by the reaction of ligands and corresponding metal salts, respectively, and characterized by X-ray diffraction and elemental analysis. Both crystals were obtained by ether diffusion and crystallized in a monoclinic system. The in vitro antimicrobial activity of the Zn(II) complexes and ligands was screened using the microplate reader method, and in vitro antitumor activities of the complexes were evaluated by MTT, with a view to developing new improved bioactive materials with novel properties. The biological activity studies of the compounds showed that the metal complexes were more active than the free ligands, and some compounds had absolute specificity for certain bacteria or cancer cell lines.